Correction: Berezowski et al. Comparison of Time-Lapse Ground-Penetrating Radar and Electrical Resistivity Tomography Surveys for Detecting Pig (Sus spp.) Cadaver Graves in an Australian Environment. Remote Sens. 2024, 16, 3498 - Victoria Berezowski; Xanthé Mallett; Dilan Seckiner; Isabella Crebert; Justin Ellis; Gabriel C. Rau; Ian Moffat (Remote Sensing)
In the original publication [...]